1997
DOI: 10.1113/jphysiol.1997.sp022048
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanism of the effects of hydrogen peroxide in rat ventricular myocytes.

Abstract: 1. Whole-cell and amphotericin-perforated patch-clamp techniques have been used to study the effects of hydrogen peroxide (H202) on action potentials and underlying ionic currents in single myocytes from the ventricles of adult rat hearts. 2. The results obtained differed markedly depending on the recording method utilized.Conventional 6. The possibility that protein kinase C (PKC) is an intracellular second messenger for the observed effects of H202 was examined using the blocker bisindolylmaelimide (BIS; 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
151
3
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 41 publications
(51 reference statements)
13
151
3
1
Order By: Relevance
“…Although previous studies have observed a persistent inward Na ϩ current during oxidative stress 25 and exposure to hydrogen peroxide (H 2 O 2 ), 26 we did not observe a noninactivating component during exposure to t-BHP or IsoK. This could be attributable to differences in mechanism of action (t-BHP and IsoK, but not H 2 O 2 , are localized in the membrane) or species differences.…”
Section: Channel Availabilitycontrasting
confidence: 53%
“…Although previous studies have observed a persistent inward Na ϩ current during oxidative stress 25 and exposure to hydrogen peroxide (H 2 O 2 ), 26 we did not observe a noninactivating component during exposure to t-BHP or IsoK. This could be attributable to differences in mechanism of action (t-BHP and IsoK, but not H 2 O 2 , are localized in the membrane) or species differences.…”
Section: Channel Availabilitycontrasting
confidence: 53%
“…Here, we show in computational simulations and supporting evidence from experiments of isolated myocytes that this irregularity is dynamical chaos, i.e., irregular dynamics from a deterministic system. EADs were induced in patch-clamped isolated rabbit cardiac myocytes by exposure to 1 mM H 2 O 2 , which promotes EADs by enhancing inward currents during repolarization, including the late Na ϩ current and the L-type Ca 2ϩ current (13,25,26). At different pacing cycle lengths (PCLs), we observed different EAD pat-terns with 1 example shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However in literature the data concerning the effect of ROS on potassium current are controversal. For example, Cerbai et al (1991) and Ward & Giles (1997) did not observe any effect, in contrast to Tarr & Valenzeno (1989) who obtained a decrease in the outward, delayed rectifier potassium current. The results of Hasan et al (2007) suggest that oxidative stress, which inhibits the delayed-rectifier current, can alter neural activity.…”
Section: Wwwintechopencommentioning
confidence: 92%